Physical properties of strontium barium niobate thin films prepared by polymeric chemical method - Melo, M. [UNESP]; Araujo, E. B. [UNESP]; Turygin, A. P.; Shur, V. Ya.; Kholkin, A. L. (Taylor & Francis Ltd, 2016)
Randomly oriented Sr0.75Ba0.25Nb2O6 thin films have been deposited on Pt(111)/Ti/SiO2/Si substrates using a polymeric chemical method to study their physical properties. Refinements of the structure confirm the stoichiometry of the studied films. The relaxor behavior is evidenced by the dielectric measurements and Vogel-Fulcher analysis of the dielectric curves. Lowering the transition temperature (T-m) by about 100K and asymmetries in the local hysteresis loops well above T-m are discussed in terms of the existence of complex defects in thin films.
Keywords: Relaxor; hysteresis loop; dielectric measurement; SBN